Heat Transfer Analysis for Non-linear Boundary Driven Flow Over a Curved Stretching Sheet With a Variable Magnetic Field - Sanni, Kehinde M.; Hussain, Qumar; Asghar, Saleem (Frontiers in Physics, 2020)
A 2-D boundary-layer flow induced by non-linear quadratic stretching of a curved surface of an incompressible MHD viscous fluid is investigated. Heat transfer analysis is presented including viscous dissipation and thermal radiation. Radially variable magnetic field is applied that satisfies the Maxwell’s equation and incorporates the curvature effects. New similarity variable and similarity transformation are introduced to reduce the governing PDE’s into ODE’s. Numerical procedure is adopted to find the solution of momentum and energy equations. The numerical scheme is validated with the existing data. The results are illustrated graphically and discussed physically. The comparison with the literature shows a significant improvement in the existing studies.